Mechanisms governing the reactivation-dependent destabilization of memories and their role in extinction - Flavell, Charlotte R.; Lambert, Elliot; Winters, Boyer D.; Bredy, Timothy W. (Frontiers in Behavioral Neuroscience, 2013)
The extinction of learned associations has traditionally been considered to involve new learning, which competes with the original memory for control over behaviour. However, a recent resurgence of interest in reactivation-dependent amnesia has revealed that the retrieval of fear-related memory (with what is essentially a brief extinction session) can result in it’s destabilization. This review discusses some of the cellular and molecular mechanisms that are involved in the destabilization of a memory following it’s reactivation and/or extinction, and investigates the evidence that extinction may involve both new learning as well as a partial destabilization-induced erasure of the original memory trace.